Antenatal corticosteroids for maturity of term or near term fetuses: systematic review and meta-analysis of randomized controlled trials. (12th October 2016) - Saccone, Gabriele; Berghella, Vincenzo
Abstract : Objective  To evaluate the effectiveness of antenatal corticosteroids given at ≥34 weeks' gestation. Design  Systematic review with meta-analysis. Data sources  Electronic databases were searched from their inception to February 2016. Eligibility criteria for study selection  Randomized clinical trials comparing antenatal corticosteroids with placebo or no treatment in women with a singleton pregnancy at ≥34 weeks' gestation. Trials on antenatal steroids in women expected to deliver late preterm (34 0 -36 6 weeks) and trials given before planned cesarean delivery at term (≥37 weeks) were included. Data synthesis  The primary outcome was the incidence of severe respiratory distress syndrome (RDS). The summary measures were reported as relative risks or mean differences with 95% confidence intervals. Results  Six trials, including 5698 singleton pregnancies, were analyzed. Three included 3200 women at 34 0 -36 6 weeks' gestation and at risk of imminent premature delivery at the time of hospital admission. The three other trials included 2498 women undergoing planned cesarean delivery at ≥37 weeks. Overall, infants of mothers who received antenatal corticosteroids at ≥34 weeks had a significantly lower risk of RDS (relative risk 0.74, 95% confidence interval 0.61 to 0.91), mild RDS (0.67, 0.46 to 0.96), moderate RDS (0.39, 0.18 to 0.89), transient tachypnea of the newborn (0.56, 0.37 to 0.86), severe RDS (0.55, 0.33 to 0.91), use of surfactant, and mechanical ventilation, and a significantly lower time receiving oxygen (mean difference −2.06 hours, 95% confidence interval −2.17 to −1.95), lower maximum inspired oxygen concentration (−0.66%, −0.69% to −0.63%), shorter stay on a neonatal intensive care unit (−7.64 days, −7.65 to −7.64), and higher APGAR scores compared with controls. Infants of mothers who received antenatal betamethasone at 34 0 -36 6 weeks' gestation had a significantly lower incidence of transient tachypnea of the newborn (relative risk 0.72, 95% confidence interval 0.56 to 0.92), severe RDS (0.60, 0.33 to 0.94), and use of surfactant (0.61, 0.38 to 0.99). Infants of mothers undergoing planned cesarean delivery at ≥37 weeks' gestation who received prophylactic antenatal corticosteroids 48 hours before delivery had a significantly lower risk of RDS (0.40, 0.27 to 0.59), mild RDS (0.43, 0.26 to 0.72), moderate RDS (0.40, 0.18 to 0.88), transient tachypnea of the newborn (0.38, 0.25 to 0.57), and mechanical ventilation (0.19, 0.08 to 0.43), and significantly less time receiving oxygen (mean difference −2.06 hours, 95% confidence interval −2.17 to −1.95), lower percentage of maximum inspired oxygen concentration (−0.66%, −0.69% to −0.63%), shorter stay in neonatal intensive care (−7.44 days, −7.44 to −7.43), and a higher APGAR score at one and at five minutes. Conclusions  Antenatal steroids at ≥34 weeks' gestation reduce neonatal respiratory morbidity. A single course of corticosteroids can be considered for women at risk of imminent late premature delivery 34 0 -36 6 weeks' gestation, as well as for women undergoing planned cesarean delivery at ≥37 weeks' gestation. Systematic review registration  PROSPERO CRD42016035234.